2022
DOI: 10.1080/13880209.2022.2117828
|View full text |Cite
|
Sign up to set email alerts
|

Shenlian extract attenuates myocardial ischaemia-reperfusion injury via inhibiting M1 macrophage polarization by silencing miR-155

Abstract: Context Shenlian extract (SL) is a combination of Salvia miltiorrhiza Bge. (Labiatae) and Andrographis paniculata (Burm. F.) Wall. Ex Nees (Acanthaceae) extracts, which promote blood circulation and clear endogenous heat toxins. Myocardial ischaemia-reperfusion injury (MI/RI) is aggravated myocardial tissue damage induced by reperfusion therapy after myocardial infarction. Objectives This study explores the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition, previous studies have revealed that silencing miR-155 can inhibit M1 macrophage polarization that reduces inflammation. 41 , 42 Our work focused on M1 macrophage-derived exosomal miR-155 entering β cells and contributing to β cell dysfunction, in which we neglected the effect of miR-155 sponge on M1 macrophage polarization that might also delay the progression of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have revealed that silencing miR-155 can inhibit M1 macrophage polarization that reduces inflammation. 41 , 42 Our work focused on M1 macrophage-derived exosomal miR-155 entering β cells and contributing to β cell dysfunction, in which we neglected the effect of miR-155 sponge on M1 macrophage polarization that might also delay the progression of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…MCPIP is not only expressed in CMs but plays an essential role in myocardial cells during inflammation after MI by down-regulating miR-155 and NF-κB signaling ( Figure 1 ) [ 45 ]. miR-155 regulates the differentiation and polarization of macrophages through the JAK2/STAT3 signaling pathway, particularly targeting SOC3 ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 ].…”
Section: The Emerging Impact Of Non-coding Rnas’ Regulation Of Cardia...mentioning
confidence: 99%
“…Among them, the miRNAs in macrophage polarization, have received widespread attention from domestic and foreign scholars, and some important progress has been made. First, as a star miRNA, miRNA-155 has been widely studied for its role in macrophage polarization, and many studies so far revealed that miRNA-155 was involved in promoting M1 polarization ( 60 65 ), for example, the expression of miRNA-155 was significantly upregulated when macrophages polarized to the M1 phenotype, however, its expression was obviously downregulated when macrophages polarized to M2 phenotype. In addition, silencing miR-155 significantly promoted the polarization of M2 macrophages, and overexpression of miRNA-155 could induce a switch from M2 to M1 phenotype ( 60 ).…”
Section: The Role Of Mirnas In Macrophage Polarizationmentioning
confidence: 99%
“…Besides, miR-155-5p can regulate M1 polarization by other pathways, such as SOCS1/NF-κB pathway ( 63 ), and let-7a-5p can also target suppressor of cytokine signaling 1 (SOCS1) to modulate NF-κB, and activate M1 macrophages ( 64 ). Shenlian extract was demonstrated to inhibit the M1 polarization by inhibiting miR-155, upregulating SOCS3 and blocking the JAK2/STAT3 signaling pathway, thereby reducing tissue damage and cell apoptosis ( 65 ). Another literature study on the role of miRNA-155 in macrophage polarization suggested that miR-155 could induce M1 polarization by way of directly targeting the IL13Rα1 (IL-13 receptor α 1, IL13Rα1), which interferes with the activation of STAT6 and indirectly regulates the expression of other M2 related genes ( 66 ).…”
Section: The Role Of Mirnas In Macrophage Polarizationmentioning
confidence: 99%